Astragaloside IV inhibits platelet-derived growth factor-BB-stimulated proliferation and migration of vascular smooth muscle cells via the inhibition of p38 MAPK signaling - CHEN, ZHUO (D.A. Spandidos, 2014)
Astragaloside IV (AS-IV), the major active component extracted from Astragalus membranaceus, has been demonstrated to exhibit protective effects on the cardiovascular, immune, digestive and nervous systems; thus, has been widely used in traditional Chinese medicine. Abnormal proliferation and migration of vascular smooth muscle cells (VSMCs) is closely associated with the initiation and progression of cardiovascular diseases, including atherosclerosis and restenosis. However, the effects of AS-IV on VSMCs remain unknown. For the first time, the present study demonstrated that AS-IV markedly suppressed platelet-derived growth factor (PDGF)-BB-stimulated cellular proliferation and migration of HDMEC-a human dermal VSMCs (HDVSMCs). Further investigation into the underlying molecular mechanisms demonstrated that the administration of AS-IV attenuated the PDGF-BB-stimulated switch of HDVSMCs into a proliferative phenotype. Furthermore, AS-IV inhibited the PDGF-BB-induced expression of cell cycle-associated proteins, as well as the upregulation of matrix metalloproteinase (MMP)2, but not MMP9. In addition, AS-IV was shown to downregulate the activation of p38 mitogen-activated protein kinase (MAPK) signaling induced by PDGF-BB in HDVSMCs. Therefore, the observations of the present study indicate that AS-IV inhibits PDGF-BB-stimulated VSMC proliferation and migration, possibly by inhibiting the activation of the p38 MAPK signaling pathway. Thus, AS-IV may be useful for the treatment of vascular diseases.